2014
DOI: 10.1111/nph.13017
|View full text |Cite
|
Sign up to set email alerts
|

The standard centrifuge method accurately measures vulnerability curves of long‐vesselled olive stems

Abstract: SummaryThe standard centrifuge method has been frequently used to measure vulnerability to xylem cavitation. This method has recently been questioned. It was hypothesized that open vessels lead to exponential vulnerability curves, which were thought to be indicative of measurement artifact.We tested this hypothesis in stems of olive (Olea europea) because its long vessels were recently claimed to produce a centrifuge artifact. We evaluated three predictions that followed from the open vessel artifact hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(113 citation statements)
references
References 56 publications
(151 reference statements)
6
106
0
1
Order By: Relevance
“…However, we note that the long-vessel artefact has been rebutted by other studies Hacke et al 2014), and this issue remains unresolved. (2) To avoid artefactual embolism induction caused by the cutting of a branch, while the xylem is under tension, rehydration/relaxation of samples has been suggested, followed by re-cutting under degassed water (Wheeler et al 2013), although this artefact has not been found by others (Venturas et al 2015).…”
Section: Methodological Precautionsmentioning
confidence: 69%
“…However, we note that the long-vessel artefact has been rebutted by other studies Hacke et al 2014), and this issue remains unresolved. (2) To avoid artefactual embolism induction caused by the cutting of a branch, while the xylem is under tension, rehydration/relaxation of samples has been suggested, followed by re-cutting under degassed water (Wheeler et al 2013), although this artefact has not been found by others (Venturas et al 2015).…”
Section: Methodological Precautionsmentioning
confidence: 69%
“…For this reason, most of our sample set was taken from the conifer clade, using the same individuals for both optical (sampled in 2016) and cavitron (sampled in 2012) techniques. The accuracy of centrifuges for measuring angiosperm xylem vulnerability is the subject of considerable debate due to probable artifacts associated with long vessels (Torres-Ruiz et al, 2014;Hacke et al, 2015). For this reason, we only measured two species of angiosperms, selected to cover a range of sensitivities to water stress but both of which had maximum xylem vessel lengths that were approximately half that of the rotor diameter.…”
Section: Discussionmentioning
confidence: 99%
“…The most likely cause of this artifact is that microbubbles, which move into the sample either prior to, or during, the spinning phase lead to embolism formation when they reach the center of the sample where centrifugal forces are highest (Wang et al, 2014). This open-vessel artifact has been the subject of intense debate, with some researchers suggesting that the artifact only affects the Cavitron version of the centrifuge technique and not the static centrifuge method Jacobsen and Pratt, 2012;Sperry et al, 2012;Tobin et al, 2013;Hacke et al, 2015). Data from this study demonstrate that static and spin centrifuge techniques produced similarly biased results for Q. robur.…”
Section: Speciesmentioning
confidence: 99%
“…Samples were spun to five xylem tensions ranging between 20.3 and 23.5 MPa. Foam pads saturated with perfusing solution were added to reservoirs in the centrifuge rotor in order to ensure that the cut ends of samples remained immersed in water during spinning (Hacke et al, 2015). Measurements of hydraulic conductance between spins were made using a Sartorious Practum analytical balance (0.01 mg resolution) connected to a computer with a custom program recording flow and computing conductance (Graviflow; University of Bordeaux).…”
Section: Vulnerability Curves Based On Hydraulic Measurementsmentioning
confidence: 99%